Biochemical Profile and Bio-Concentration of Cu, Hg, Pb and Zn in Tilapia guineensis inhabiting Lagos lagoon, Nigeria - Ajibare, Adefemi; Loto, Olajide (Food and Applied Bioscience Journal, 2023)
This study investigated Aspartate aminotransferase (AST), Alanine aminotransferase (ALT) and Alkaline Phosphatase (ALP) in the liver tissue as well as bio-concentration of Zn, Cu, Pb and Hg in Tilapia guineensis inhabiting Lagos lagoon, Nigeria. Serum biochemical enzymes were determined using calorimetric assay and phenolphthalein monophosphate method while heavy metals by atomic absorption spectrophotometry. The concentration of biochemical enzymes were in the order of ALP>AST>ALT. The AST and ALT ranged from 59.20 ± 21.03IU/L to 108.33 ± 30.48IU/L and 21.87 ± 7.49IU/L to 81.44 ± 37.09IU/L (means of 88.56 ± 33.38IU/L and 48.94 ± 33.48IU/L respectively) while the mean ALP in the fish was 113.55 ± 82.33IU/L (minimum and maximum of 43.47 ± 17.50IU/L and 183.09 ± 91.16IU/L respectively). The concentration of Cu, Zn, Hg and Pb in water was 1.88 ± 2.94mg/L, 25.49 ± 44.27mg/L, 0.00 ± 0.00mg/L and 0.25 ± 0.49mg/L respectively. Also, the concentration of Cu, Pb, Hg and Zn in T. guineensis of Lagos lagoon was 0.0093 ± 0.01mg/kg, 0.0005 ± 0.00mg/kg, 0.0000 ± 0.00mg/kg and 0.0248 ± 0.04mg/kg respectively. The Bio-Concentration factor was as low as 0.00 (Hg), 0.005 (Cu), 0.002 (Pb) and 0.001 (Zn). The result also revealed negative correlation (r= -0.06, P=0.85) between AST and Cu in fish. Similarly, ALT was significantly correlated with Cu (r=0.66, P=0.02), Pb (r= -0.59, P=0.05) and Hg (r= -0.63, P=0.03) in water. This study established that metals’ concentrations imposed negative effects on the enzymes.